Health and physical activity of students - Pavliuk, Iryna; Khomitska (Lyashenko), Valentyna (My University, 2022)
In recent years, there has been a sharp deterioration in the health and physical fitness of students. Only about 10% adolescents can be considered healthy, more than 40% suffer from chronic diseases. Diseases of the cardiovascular and musculoskeletal systems are rapidly progressing, which are largely due to insufficient physical activity of children. More than 50% of girls and boys, graduating from school, already have two or three chronic diseases, and in general, only 15% of graduates can be considered practically healthy. Preserving the health of young people today is a priority for the state. One of the most important tasks facing universities, as noted M.Ya. Vilensky, S.P. Evseev is to maintain the optimal state of health of students and, in this regard, it is necessary to create an appropriate training system. The decrease in the health level of the younger generation, the increase in the number of students belonging to a special medical group require closer attention to the organization of the educational process in physical culture. В останні роки спостерігається різке погіршення стану здоров'я і фізичної підготовки учнів. Тільки близько 10% підлітків можна вважати здоровими, більше 40% страждають хронічними захворюваннями. Стрімко прогресують захворювання серцево-судинної і опорно-рухової систем, які багато в чому обумовлені недостатньою фізичною активністю дітей. Більше 50% дівчат і хлопчиків, які закінчують школу, вже мають два-три хронічних захворювання, і в цілому практично здоровими можна вважати тільки 15% випускників. Збереження здоров'я молоді сьогодні є пріоритетом для держави. Одне з найважливіших завдань, що стоять перед університетами, як зазначав М.Я. Віленський, С.П. Євсєєв полягає в підтримці оптимального стану здоров'я учнів і, в зв'язку з цим, необхідно створити відповідну систему навчання. Зниження рівня здоров'я підростаючого покоління, збільшення кількості учнів, що належать до особливої медичної групи, вимагають більш пильної уваги до організму.
Keywords: здоров'я; рухова активність; health; physical activity; кафедра фізичного виховання